Analysis of Government Policies in Padang City in Food Waste Management at the Household Level - Rahman, Defri; Elfindri, Elfindri; Henmaidi, Henmaidi; Rahman, Hafiz (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
The waste management issue in the city of Padang, particularly the increasing accumulation of household waste, with the predominant composition being food waste, is the primary focus of this research. The research aims to investigate the policies and strategies implemented by the Padang municipal government in managing household food waste. The research method employed is qualitative, involving data collection through interviews, observations, and direct documentation. The research results indicate that the management of household food waste is still integrated within the broader framework of urban waste management. The absence of specific governance for household food waste results in a significant increase in the amount of food waste being disposed of directly in the Final Disposal Site (TPA). The study concludes that: 1) the management of household food waste is intertwined with urban waste management; 2) Specifically, the Padang city government has not yet implemented a program for managing household food waste; 3) The absence of governance for household food waste leads to a high volume of food waste being directly disposed of in the TPA; 4) Specifically, there is currently no program related to food waste reduction.